Calidad de vida y funcionalidad familiar en pacientes con diabetes mellitus tipo 2. del Hospital Belén de Trujillo, 2018 - Palomino Cuicapoza, Elsa Carmen (2019)
Abstract: In the study entitled "Quality of life and family functioning of the patients diabetes mellitus type 2 at Hospital Belen de Trujillo 2018 " had as a general objective to determine the relationship that exists between the quality of life and family functioning of of the patients diabetes mellitus type 2 at Hospital Belen de Trujillo 2018; the type of study was correlational of non-experimental crosssectional design; whose population was made up of 100 patients. The technique used was the structured interview and the instrument was the questionnaire of the two variables, the quality of life questionnaire Diabetes 39 and the other variable Family functioning (Apgar family test) prepared by Gabriel Smilkstein, the two reliable and validated instruments. The result was that 70,94 % of the patients affected their quality of life and 64,4% of families have a family functioning of médium and balanced range and 35,6% of extreme range. It is concluded that there is a relationship between the quality of life and the family functioning of patients with type 2 diabetes mellitus at Hospital Belén de Trujillo 2018